Mantle and Crustal Xenoliths in a Tephriphonolite From La Palma (Canary Islands): Implications for Phonolite Formation at Oceanic Island Volcanoes - Klügel, Andreas; Albers, Elmar; Hansteen, Thor H. (Frontiers in Earth Science, 2022)
The occurrence of mantle-derived peridotite xenoliths in phonolitic melts is a rare phenomenon, and is commonly ascribed to a mantle origin of the phonolite. The alternative possibility, that xenoliths are transported into evolving phonolite melts by mafic magmas, has received little attention. A unique tephriphonolite lava with phonolitic groundmass composition, from the active Cumbre Vieja volcano of La Palma (Canary Islands), allows to test these models. The lava contains abundant inclusions that represent the island’s major xenolith types: kaersutite-dominated cumulates, gabbros from the lower oceanic crust, and peridotites from the mantle. Our petrological investigations indicate that the tephriphonolite magma contained 3–4 wt% H2O and was stored in the lower crust at around 250–350 MPa and 900–950°C, at oxidized conditions (∆NNO of 2–3). The peridotite xenoliths are mantled by complex polyphase selvages, with adjacent up to 1.6 mm wide zonations where olivine compositions change from Fo78-86 at the selvage contact to Fo89-91 inside the xenoliths. We carried out diffusion modelling for Fe-Mg exchange and found that the peridotites had contact with intermediate to evolved alkaline melts over decades to centuries. This timescale is comparable to that inferred for basanite-hosted peridotite xenoliths from Cumbre Vieja. The following model is proposed: differentiation of evolved melts occurs in a magma accumulation zone in the lowermost oceanic crust beneath La Palma. The evolving melts receive periodic recharge by mantle-derived mafic magmas at intervals on the order of decades to a few centuries, comparable to historic eruption recurrences (80 years on average). Some of these recharge pulses carry mantle peridotite fragments that become deposited in the accumulation zone. Thus, these xenoliths do not reflect formation of the evolved melts in the mantle. Final ascent of the tephriphonolite was triggered by magma recharge some weeks before its eruption, resulting in entrainment and thorough mingling of a mixed xenolith population (cumulates, oceanic crust gabbros, peridotites). We infer that formation of phonolites in the lower crust beneath oceanic island volcanoes, and subsequent eruption, requires a balance between rates and volumes of magma recharge pulses and of eruptive events.